The Use of Phonics-based Instruction to Develop English Pronunciation Skills of Grade 2: The Use of Phonics-based Instruction to Develop English Pronunciation Skills of Grade 2 - Charoenrach, Rawisuda; Porntaweekul , Satjatam (RATANABUTH JOURNAL, 2026)
The objectives of this research were: 1) to develop phonics-based learning activities for enhancing the English pronunciation skills of Grade 2 students to meet the efficiency criterion of 80/80; 2) to compare students' English pronunciation skills before and after the implementation of phonics-based instruction; and 3) to investigate students' satisfaction towards the phonics-based learning activities. The sample consisted of 32 Grade 2/1 students from Wassanasuksa School, Wang Sam Mo District, Udon Thani Province, under the Office of the Private Education Commission, during the 2025 academic year. The participants were selected through purposive sampling. The research instruments included: 1) seven phonics-based lesson plans; 2) a 15-item English pronunciation test; and 3) a 15-item student satisfaction scale. Data were analyzed using mean, standard deviation, percentage, and Wilcoxon Signed Ranks Test. The research findings revealed that: 1) The efficiency of the phonics-based learning activities was 83.78/81.53, which exceeded the established 80/80 criterion. 2) The English pronunciation skills of Grade 2 students after participating in the phonics-based instruction were significantly higher than those before the instruction at a .05 level of statistical significance (Z = -4.947, p < .001). And 3) The overall satisfaction of Grade 2 students towards the phonics-based learning activities was at a high level (x̅ = 4.25, S.D. (0.87)).